2020
DOI: 10.1371/journal.pone.0235628
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus low-molecular-weight heparin for venous thromboembolism prophylaxis in orthopaedic trauma patients: A patient-centered randomized controlled trial

Abstract: Background Emerging evidence suggests aspirin may be an effective venous thromboembolism (VTE) prophylaxis for orthopaedic trauma patients, with fewer bleeding complications. We used a patient-centered weighted composite outcome to globally evaluate aspirin versus low-molecular-weight heparin (LMWH) for VTE prevention in fracture patients. Methods We conducted an open-label randomized clinical trial of adult patients admitted to an academic trauma center with an operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…Moreover, SSI definitions demonstrate variety across the studies in the literature, further compromising the comparisons of pooled results. Finally, most publications have investigated VTE prophylaxis within a specific subset of the orthopaedic population: those undergoing TJA surgery 347 . Considering that most of the relevant current published evidence demonstrates heterogeneity and a high risk of bias, additional level one studies are needed to truly evaluate the associations between VTE prophylaxis and SSI across all orthopaedic surgery subspecialties 350 .…”
Section: - Does the Type Of Vte Prophylaxis Influence The Risk Of Sub...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SSI definitions demonstrate variety across the studies in the literature, further compromising the comparisons of pooled results. Finally, most publications have investigated VTE prophylaxis within a specific subset of the orthopaedic population: those undergoing TJA surgery 347 . Considering that most of the relevant current published evidence demonstrates heterogeneity and a high risk of bias, additional level one studies are needed to truly evaluate the associations between VTE prophylaxis and SSI across all orthopaedic surgery subspecialties 350 .…”
Section: - Does the Type Of Vte Prophylaxis Influence The Risk Of Sub...mentioning
confidence: 99%
“…No difference was identified in infection rates between the two groups, but patients were nearly eight times more likely to experience a wound complication whilst receiving LMWH as opposed to ASA. Haac et al, recently conducted an open-label RCT of adult patients admitted to an academic trauma center with operative extremity fractures, or a pelvis or acetabular fracture, comparing ASA with LMWH 347 . Deep infections were identified in 4.3% of patients receiving ASA, and in 5.5% in those receiving LMWH.…”
Section: - Does the Type Of Vte Prophylaxis Influence The Risk Of Sub...mentioning
confidence: 99%
“…Thromboprophylaxis for our patients was, in keeping with current national guidelines, undertaken with one of two agents for differing time periods. We did not collect data on how many patients were prescribed either dalteparin or aspirin on discharge, though notably, large-scale meta-analyses and randomised controlled trials have shown no difference in the clinical effectiveness of these agents following both lower limb arthroplasty and trauma [31][32][33]; hence, we would not expect any difference in effectiveness of these agents in our cohort. Equally, we did not extend the thromboprophylaxis regimen in the TKA group to 5 weeks, as this would expose this cohort to a risk of complications for no benefit in terms of reduced VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…The study is designed to enrol 12 200 patients. Assuming an estimated risk of death in the LMWH arm of 1.0%, 37 38 the proposed sample size provides 95% power to demonstrate the non-inferiority of aspirin with a non-inferiority margin of 0.75% at the upper bound of a two-sided 96.2% CI, as compared with LMWH. These calculations account for two interim analyses and allow for an attrition rate up to 7.5%.…”
Section: Methods and Analysismentioning
confidence: 99%